Design, Biological and Theoretical Study of New Mixed Ligands Complexes of Schiff Base Derived from Sulfabenzamide and 1,10-phenanthroline - Abboud, Maryam H.; Baqer, Shaymaa R. (Iraqi Journal of Science, 2025)
A new Schiff base ligand was prepared via a condensation reaction. The synthesis involved combining N-(4-aminophenylsulfonyl) benzamide (also known as sulfabenzamide) with indoline-2,3-dione. To facilitate the reaction, three drops of glacial acetic acid were added. This process yielded the ligand N-(4-(2-oxoindoline-3-ylideneamino) phenylsulfonyl) benzamide, designated as (L). Mixed ligand complexes were prepared in a molar ratio (1:1:1) (M:1,10-phen, L) at concentrations of 10-4M by interacting L and 1,10-phenanthroline, with the following metal ions (Cr+3, Mn+2, Zn+2, Pd+2, Cd+2, Pt+4). These complexes exhibited different geometric shapes, including (octahedral for both Cr+3, Mn+2, Pt+4, tetrahedral for Zn+2 and Cd+2, and square planar for Pd+2) . These prepared complexes were characterized by several techniques such as C.H.N.S, FT-IR, molar conductivity, UV-Vis spectra, magnetic susceptibility and atomic absorption. The ligands were characterized by FT-IR, UV-visible,1H-NMR, 13C-NMR, C. H. N. S and mass spectra. The results showed that the ligand (L) behaves as a bidentate chelating ligand that binds to metal ions through donor N, and O atoms. The biological activity of ligand (L,1,10-phen) and mixed ligands complexes was evaluated against two types of bacteria (positive and negative) and one type of fungi at a concentration of 0.02M. The results demonstrated that the prepared complexes have high inhibition of all types of bacteria and fungi compared to the standard drug and the ligand (1,10-phen). The standard heat of formation and binding energy for ligand (L) and all complexes produced were calculated using the Hyper-Chem8.0.7 program. Additionally, the vibration frequencies as well as the HOMO and LUMO were studied for the ligand alone. When comparing the practical and theoretical vibration frequencies of the ligand, it was found that the results of the theoretical study and experimental were close in result to the error rate within the permissible range.